Agronomic Management of Faba Bean (Vicia faba L.): A Review - Babli Rani Deb; Swapan Kumar Paul (Turkish Journal of Agriculture: Food Science and Technology)
The faba bean (Vicia faba L.) is a winter crop that can be cultivated as a versatile crop. It’s yield and quality being strongly influenced by environmental and agronomic factors, nutritional content, medicinal properties, and ability to fix nitrogen biologically. Therefore, to maximize advantages of faba bean cultivation, choosing the appropriate varieties, planting times, techniques, plant density, depth of sowing, and ensuring proper crop nutrients and irrigation is essential. For successful faba bean production in subtropical climates, it's important to assess the performance of different varieties under these specific conditions. Planting dates and soil temperature are crucial for germination, growth, and yield. At the same time, the crop's performance is also influenced by sowing methods, plant density, sowing depth, and water and fertilizer management. Integrating faba beans into cropping systems is expected to offer various ecological benefits. This paper reviews the existing literature on the agronomic practices of faba beans.